2012
DOI: 10.2337/dc11-1343
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effects of a Mindfulness-Based Stress-Reduction Intervention in Type 2 Diabetic Patients

Abstract: OBJECTIVETo determine whether a mindfulness-based stress reduction (MBSR) intervention is effective for reducing psychosocial distress (i.e., depression, psychosocial stress) and the progression of nephropathy (i.e., albuminuria) and for improving the subjective health status of patients with type 2 diabetes.RESEARCH DESIGN AND METHODSPatients with type 2 diabetes and microalbuminuria were randomized to a mindfulness-based intervention (n = 53) or a treatment-as-usual control (n = 57) group. The study is desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(177 citation statements)
references
References 11 publications
4
147
0
19
Order By: Relevance
“…Restructuring of cognitive appraisal using mindfulness brings about positive adaptation outcomes, such as mitigating the patient's stress and helping them to control and resolve their problems. This involves a decentralization strategy: acknowledgement of the current situation, attention, non-judgmental acceptance of the situation, and avoidance of negative thinking [10][11] [12]. The schematic model of this conceptual frame is shown in Figure 1.…”
Section: Mindfulness As a Coping Resource For Hemodialysis Patientsmentioning
confidence: 99%
“…Restructuring of cognitive appraisal using mindfulness brings about positive adaptation outcomes, such as mitigating the patient's stress and helping them to control and resolve their problems. This involves a decentralization strategy: acknowledgement of the current situation, attention, non-judgmental acceptance of the situation, and avoidance of negative thinking [10][11] [12]. The schematic model of this conceptual frame is shown in Figure 1.…”
Section: Mindfulness As a Coping Resource For Hemodialysis Patientsmentioning
confidence: 99%
“…La revisión bibliográfica y los datos obtenidos del GHQ en el momento inicial aconsejaron dedicar una parte del programa de intervención a técnicas psicológicas para el tratamiento de los síntomas hallados, tales como meditación, relajación y visualización (Hartmann et al, 2012) y a ejercicios como el Qigong (Liu et al, 2010) que han dado muestras de mejorar el bienestar psíquico de estos pacientes.…”
Section: Discussionunclassified
“…Tenía una duración de 15 minutos e incluía, alternativamente, técnicas de relajación (Relajación Progresiva de Jacobson y Entrenamiento Autógeno de Schultz) y visualización de situaciones positivas y meditación (Hartmann et al, 2012).…”
Section: Procedimientounclassified
See 1 more Smart Citation
“…Mindfulness-based training, along with integration of meditation and physical checking techniques, can help raise of awareness of thoughts, feelings, and automated physical senses, so that one can go out of the automated mode using the techniques and behave mindfully and be in moment 15 . Hartmann et al 16 have found in a study that mindfulness based on stress reduction can affect the reduction of emotional distress (depression and anxiety) in types of chronic diseases positively. According to the positive effects of mindfulness-based cognitive therapy in the field of treatment of psychiatric disorders, the aim of this study is to investigate the effectiveness of mindfulness-based cognitive therapy in reducing anxiety and depression of a women victim of domestic violence in Tehran.…”
Section: Introductionmentioning
confidence: 99%